Conflict management style: do personality and gender matter? - Hassan, Arif; Singh, Nirmala (Assert, India, 2013)
The paper examines the role of big five personality traits and gender on conflict management styles. It was expected that females prefer non-confrontational whereas males opt more for confrontational modes of conflict resolution. It was also expected that personality traits will significantly predict choice of conflict management styles. The data were collected from 270 undergraduate students (Males = 160; Females = 110) with the help of standardised instruments to measure the study variables. The result supported most of the hypotheses. Significant gender differences were found in the use of competing, and compromising styles of conflict management where females favoured compromise while males opted competition. Among the personality traits extraversion positively contributed to competing as well as problem solving and negatively to yielding, and avoiding styles. Agreeableness was positively related to yielding, compromising, and problem solving and negatively to competing style. Conscientiousness promoted problem solving style of conflict management. Neuroticism was positively associated with avoiding and negatively with compromising and problem solving styles. Openness to experience promoted problem solving as well as compromising styles and negatively predicted avoiding style. The result provides empirical support to the big five personality construct in predicting conflict handling behaviour.